STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MELAKSANAKAN PEMBINAAN MORAL KEAGAMAAN SISWA: STUDI KASUS SMK SARASWATI - Junedi Junedi; Kabul Laksono; Mukh Nursikin (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
This study aims to determine the strategy of Islamic religious education teachers in carrying out student religious moral development: a case study of SMK Saraswati Salatiga. In this study using qualitative methods sourced from the method of observation, interviews, and documentation. The data collection used in this study was carried out through primary data and secondary data, namely in the form of observations and interviews with school principals, Islamic religious education teachers, and students. These findings indicate that the implementation of student religious moral development carried out by Islamic religious education teachers in schools includes extra-school and social activities, congregational prayers, and reading the Koran and Asmaul Husna. Through this strategy, the implementation of the religious moral development of students at the Saraswati Salatig Vocational School is going well and is an action that is an affective rational action, traditional rationale, and oriented to religious values.